Avaliação técnico-financeira de um cultivo da ostra-do-mangue, Crassostrea brasiliana (Lamarck, 1818), na comunidade de Graciosa, Município de Taperoá, Bahia - Gradvohl, Marcel Philippe Gerard Monte (2014)
The oyster stands out as an aquatic resource of great economic and social interest for the Southern Bahia subregion because of its present relevant natural and geographical conditions for establishment of enterprises of this nature. This research work aims to analyze the technical and financial aspects of cultivating the mangrove oyster, Crassostrea brasiliana (Lamarck, 1818), in the community of Graciosa, Taperoá, Bahia State, and to create financial controls for fully efficient management of household productive enterprises. This is justified by the fact that they are incipient and scarce economic and financial information that provide the correct development of such activities. The methodology used in this study drew on a descriptive exploratory study with a technical analysis of qualitative and quantitative approach, based on weekly visits in situ techniques, application of a semi-structured questionnaires carried out from January to December, 2013, through interviews with leaders of the oyster farming system. The production system adopted is floating through the use of long-line and lanterns, employing low-tech and seed oysters are collected at the site of cultivation itself, with an average size of 2 ± 0.5 cm. The cultivation under the current conditions shows no economic viability as highlighted by the poor estimated financial indices. It has low profitability and profitability, respectively 6.93% and 3.17 %, with the selling price of oysters at R$ 193.85 per thousand. The profit only happens when at least 92.55 % of oysters are marketed. The months of the year 2013 which had higher billings were January, November and December, with a fall in trade of oysters in the months of greater rainfall in the studied subregion being noticed. Financial viability will be seen when the selling price should reach R$ 250,00 per thousand and total investment return goes up on 6.1 years